Generasi gen Z setelah generasi milenial - Hanafi, Achmad (Maliki Interdisciplinary Journal, 2024)
Character formation is the result of interactions between biological and environmental factors. Biological factors include genetics inherited from parents, while environmental factors include habits and social interactions. Gen Z in Indonesia, who grew up in a time of economic crisis, face unique challenges in their personality development, including overprotection from parents which can make them more vulnerable to fear. Technological developments also have a significant impact, both positive and negative, on character education. Therefore, character education starting from an early age, monitoring the use of technology, and support from the environment and parents are very important to form a strong and positive personality.